Relations between Andalusian and Spanish-American Freemasonry in the first half of the 20th century: A view from Andalusia - Ruiz Sánchez, José Leonardo (2020)
Relations between Freemasonry in Latin America and Spain are not limited exclusively to the lodges that depended on Spanish Obediences from the other side of the Atlantic or on the Masons who sought to settle there in exile after Spain’s in 1936. With regards to Andalusia, those relationships were quite different from the latter at least at the beginning of the 20th century.